2008
DOI: 10.1021/bi701164y
|View full text |Cite
|
Sign up to set email alerts
|

Folding of the SAM Aptamer is Determined by the Formation of a K-turn-dependent Pseudoknot

Abstract: The S-adenosylmethionine (SAM) riboswitch is one of the most recurrent riboswitches found in bacteria and has three known different natural aptamers. The Bacillus subtilis yitJ SAM riboswitch aptamer is organized around a four-way junction which is characterized by the presence of a pseudoknot and a K-turn motif. By replacing the adenine involved in a Watson-Crick base pair at position 138 in the core region of the aptamer with the fluorescent analogue 2-aminopurine (2AP), we show that the ligand-induced reorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
81
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 57 publications
13
81
1
Order By: Relevance
“…23 In agreement with this model, it was previously found that the folding of the kink-turn motif located in the P2 helical domain is crucial for the structure and ligand binding activity of the SAM-I aptamer. 46,50 Our study also revealed that SAM binding to the aptamer produces a second folding transition involving the stacking of stems P1 and P4. 23 SAM binding was also previously shown to reorganize regions J1/2 and J3/4, 33,54 consistent with the formation of the native RNA-ligand complex as observed in the crystal structure.…”
Section: S-adenosylmethionine (Sam) Riboswitchessupporting
confidence: 52%
See 1 more Smart Citation
“…23 In agreement with this model, it was previously found that the folding of the kink-turn motif located in the P2 helical domain is crucial for the structure and ligand binding activity of the SAM-I aptamer. 46,50 Our study also revealed that SAM binding to the aptamer produces a second folding transition involving the stacking of stems P1 and P4. 23 SAM binding was also previously shown to reorganize regions J1/2 and J3/4, 33,54 consistent with the formation of the native RNA-ligand complex as observed in the crystal structure.…”
Section: S-adenosylmethionine (Sam) Riboswitchessupporting
confidence: 52%
“…A K-turn motif located in the P2 stem has been shown to be important for the structure and activity of the riboswitch. 45,46 The K-turn has been originally observed in the 23 rRNA and is characterized by the presence of a sharp bend in the phosphate backbone, which is important to mediate RNA tertiary structure interactions and protein…”
Section: Structure and Activity Of The Sam-i Riboswitchmentioning
confidence: 99%
“…Those studies (Blouin and Lafontaine 2007;Heppell and Lafontaine 2008) utilized the archaeal protein L7Ae. We recently found crystallographically that the B. subtilis protein YbxF is structurally homologous to L7Ae and that it binds to K-turns (Baird et al 2012).…”
Section: +mentioning
confidence: 99%
“…The motif causes the helical path to bend by ∼120°a nd is often the binding site for proteins (Klein et al 2001). K-turns are present in several riboswitch classes, including the Class-I S-adenosylmethionine (SAM-I) and lysine riboswitches, where it has been shown that K-turn integrity is essential for productive folding and ligand recognition (Blouin and Lafontaine 2007;Heppell and Lafontaine 2008). Kladwang et al (2012) and Sherman et al (2012) analyzed the effect that the presence of P0 has on the glycine riboswitch at the local, single-nucleotide level through chemical probing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Further examples have been found in mRNA (Mao et al 1999;Winkler et al 2001;Allmang et al 2002;White et al 2004) and in riboswitches (Montange and Batey 2006;Blouin and Lafontaine 2007;Heppell and Lafontaine 2008). They are very commonly found in C/D and H/ACA guide snoRNAs and in U3 snoRNA species (Kuhn et al 2002;Watkins et al 2002;Bortolin et al 2003;Marmier-Gourrier et al 2003;Rozhdestvensky et al 2003;Hamma and Ferré-D'Amaré 2004;Moore et al 2004;Szewczak et al 2005;Youssef et al 2007).…”
Section: The Occurrence Of K-turns In Rnamentioning
confidence: 99%